HackathonX 2024 An innovation platform by PETAKOM UMPSA - Logathepan, Muniyappan (UMPSA, 2024)
PEKAN, 22 November 2024 – HackathonX 2024, organised by Persatuan Mahasiswa Teknologi Komputer (PETAKOM), concluded successfully, leaving a lasting impact on students and the tech community.